So you want to be a teacher? - Sedgwick, Fred (SAGE, 2008)
If you are interested in a career in teaching but not sure where to start, this book is the perfect guide. Written for anybody considering taking an initial teacher training course, this down-to-earth book is a straightforward and very helpful manual whic.